Long-term cigarette smoke exposure and the memory ability of rats of different ages - Ibrahim, Badamasi; Taoheed, Atanda (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Cigarette smoke had been implicated in the aetiopathogenesis of certain features seen in children.Aims: The study is aimed at assessing the effects of high doses and long-term exposure to cigarette smoke (CSE) on the memory.Settings and Design: The study involved exposed and non-exposed rats.Materials and Methods: The rats were assigned into groups A, B, C and D respectively. Each group had 5 rats. Groups A was exposed to smokein uteroonly and group C from 2 to 5 months of age. Groups B and D served as the controls, respectively. Exposures to cigarette smoke was monitored at 200 PPM of carbon monoxide. Assessment of memory was done by comparing two reference time records separated by 10 minutes, obtained from the water maze task for each rat just after the entire period of exposure to cigarette smoke.Statistical Analysis Used: A pairedt-test was used to assess the differences using statistical package for the social sciences software (SPSS version 15).Results: The actual reference time records revealed a statistically significant difference between the initial and final water maze task time records. All the exposed 5-month-old rats showed the lowest repeat time records and also more predictability in their repeat time records.Conclusions: Regardless of the age at the onset and duration of exposure to cigarette smoke, all the rats were able to attain memory for the first session of water task. The 5 months of exposed rat attained more memory. Hence, long-term CSE was beneficial to memory attainment.
Keywords: Age; cigarette smoke; memory